2016
DOI: 10.17795/iji-34944
|View full text |Cite
|
Sign up to set email alerts
|

Blood-Borne Infections in Tattooed People

Abstract: Background: Tattoos are associated with blood-borne infections that result from viruses such as the hepatitis B virus (HBV), the hepatitis C virus (HCV), and the human immunodeficiency virus (HIV). This association is equally evident among people without major risk factors and among those with major risk factors like injected drug users (IDUs). Objectives: In this study we evaluated all tattooed patients admitted to our hospital (the Boo-Ali hospital in southeastern Iran) between February 2006 to January 2015.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Similar event is seen in women and girls while piercing their nose and ears they too share their needles. 20 Study participants reported of lack of sterilization or lack of change of blades at beauty parlours such as barbers and saloons. To reduce blood-borne infections such as hepatitis B, there is a need to ensure that needles used for tattoo procedures are used and disposed of appropriately while blades are sterilized before and after every shave.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Similar event is seen in women and girls while piercing their nose and ears they too share their needles. 20 Study participants reported of lack of sterilization or lack of change of blades at beauty parlours such as barbers and saloons. To reduce blood-borne infections such as hepatitis B, there is a need to ensure that needles used for tattoo procedures are used and disposed of appropriately while blades are sterilized before and after every shave.…”
Section: Discussionmentioning
confidence: 97%
“…Additionally, family structure among the people living in the study area contributes to the sharing behavior. 20 The findings of the study did not represent the entire population of Mombasa since it was performed in four treatment care centers. In fear that the researcher was to break confidentiality, the respondent might have constrained from providing information, which could potentially lead to them being victimized.…”
Section: Discussionmentioning
confidence: 99%
“…Intermediary hosts can also be infected through ingestion of oocysts and tachyzoites. 10,11 Scientia Psychiatrica Vol 1 Issue 1 https://scientiapsychiatrica.com…”
Section: Discussionmentioning
confidence: 99%
“…The negative image and dislike of tattoos cuts across the world as seen in Brazil, [ hepatitis following the procedure [19]. In a nine year study done in Iran comprising 63 patients admitted with tattoos; it was found that four (6.3%) tested positive for hepatitis B, seven (11%) tested positive for HCV, and five (7.9%) tested positive for HIV [20]. Another study in South Eastern Iran in 2005 involving 39 women with tattoos showed three cases (7.6%) positive for hepatitis B, 30.7% were HCV positive and one patient was positive for HIV [21].…”
Section: Discussionmentioning
confidence: 99%